"I Am as Fit as a Fiddle": Selling the Mugabe Brand in the 2013 Elections in Zimbabwe. Issue 3 (2nd July 2020) - Chibuwe, Albert
Abstract : Robert Mugabe's dominance in Zimbabwean politics post-independence has led critics to argue that politics in Zimbabwe is personal and patriarchal. Mugabe's ruling Zimbabwe African National Union–Patriotic Front (ZANU PF)'s alleged use of violence, violent discourse, and other unorthodox power retention strategies have been used to justify claims that Zimbabwean politics is the politics of chaos. In this post-colonial (mis)reading of African politics, ZANU PF and Mugabe discourses have been labeled nativism, patriotic history, Mugabeism, grotesque nationalism, etc. However, these studies have either been uncritically pro- or anti-ZANU PF (Moore 2012). The paper, through an analysis of ZANU PF's rebranding of Mugabe in the July 2013 elections, suggests a new multitheoretical approach to overcome this uncritical reading of Zimbabwe's political branding practices. The suggested approach utilizes insights gleaned from sign theory, political branding and/or advertising theory, post-colonial theory, and decolonial theory.